Postpartum Hemorrhage Emergency Management Using Focused Assessment With Sonography For Obstetrics (FASO): A Case Report - C. Rincón; J. Cubillos; C. Arzola (CINQUILL Medical Publishers Inc., 2019)
Postpartum hemorrhage is the leading cause of maternal death around the world according to World Health Organization [1]. While cesarean delivery is a risk factor, uterine atony is the main etiology [2]. Cesarean delivery and concomitant tubal sterilization are a known risk of postoperative intra-abdominal bleeding, which can be insidious and difficult to diagnose in the recovery period. Furthermore, a late diagnosis can lead to a less than optimal management. Point-of-care ultrasonography is an available technique that can contribute to a prompt diagnosis and accurate decision-making [3]. We present a case of a patient in postoperative care after cesarean delivery and tubal sterilization who developed hypovolemic shock symptoms, without any sign of uterine atony or vaginal bleeding. Focused assessment with sonography for obstetrics (FASO) was quickly performed in the recovery room to diagnose intra-abdominal bleeding and decision-making to perform an emergency surgical intervention.